An Eco-critical Study of the Lio Tribe's Oral Literature in Ende Regency, East Nusa Tenggara - Mboka, Idris; Anshari; Sultan (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to identify, describe, and explain the pastoral literary narrative study model in the Lio oral literature of Ende Regency, East Nusa Tenggara; identify, describe, and explain the pastoral and apocalyptic literary narratives in the Lio oral literature of Ende Regency, East Nusa Tenggara. Based on the results of research and data analysis on the Lio oral literature in Ende Regency, East Nusa Tenggara, several legends were discovered, including the Legend of Lake Lopi, the Legend of Lake Mbata, the Legend of Lake Sora, the Legend of Lake Kelimutu, the fairy tale of Queen Ji'e and Queen Re'e, and the myth of Bobi and Nombi (the goddess of rice). Based on the results of data identification using the Environmental Literature Study Model, the pastoral narrative study model and the apocalyptic narrative study model were found. The results of this analysis indicate that the pastoral narrative study model in the Lio folklore of Ende Regency, East Nusa Tenggara, ecological representation contains elements of environmental wisdom as follows. First, pastoral literature in the oral literature of the Lio Tribe represents the livelihood of village communities in Ende Regency, East Nusa Tenggara, who are generally farmers. In addition, the idyll element shows ideal behavior that refers to village environmental wisdom, namely the harmonious relationship between humans and God, the relationship between humans and other humans, and the harmonious relationship between humans and nature. The connection between humans and God in relation to environmental wisdom in the Lio Tribe is shown through the principles of life, mindset, and perspective of the community that always includes God in every activity they do that is closely related to the environment. Second, the form of nostalgia represents past memories experienced by several characters in Lio tribal folklore related to the prosperity of a region or an event. Third, the georgic element that shows the process of working in harmony with nature as something comfortable represents comfortable farming work and enjoying agricultural products. Fifth, the form of retreat and return that depicts the escape of city people to the village due to natural disasters, avoiding natural disasters, seeking a better life and colonial motives that want to control areas rich in natural resources.